Increasing the Efficiency of Electronic Commerce Insurance Services by Reducing Financial Losses - Nuralieva Mukaddas Mamurovna; Khalikulova Gulzada Tadjimuratovna (Research Parks Publishers, 2022)
This article discusses insurance services that can be scaled up with e-commerce elements. The introduction of e-commerce into the insurance sector, the emergence of technologies using the Internet have led to significant changes in the structure of increasing the efficiency of e-commerce in insurance services. Targeted research is being carried out around the world to find scientific solutions to the problems of e-commerce development and to increase its effectiveness. Research is focused on the development of electronic forms of doing business, the transition to a digital economy, the components of e-commerce and their interconnection, the security of information and payment systems. The article analyzes complex measures for the active development of the digital economy and the widespread introduction of modern information and communication technologies in all sectors and industries.